Identifying Unmet Needs of Family Dementia Caregivers: Results of the Baseline Assessment of a Cluster-Randomized Controlled Intervention Trial. - Zwingmann, Ina; Michalowsky, Bernhard; Esser, Alexander; Kaczynski, Anika; Monsees, Jessica; Keller, Armin; Hertel, Johannes; Wucherer, Diana; Thyrian, Jochen René; Eichler, Tilly; Kilimann, Ingo; Teipel, Stefan; et al. (J Alzheimers Dis, 2019)
BACKGROUND: Caregivers providing informal care for people with dementia (PwD) often report unmet needs, burden, and health impairments. Optimal support for family dementia caregivers will likely benefit from better understanding and assessment of the prevalence and types of caregivers' unmet needs and associated socio-demographic and clinical characteristics. OBJECTIVE: The present study investigates 1) the number and types of caregivers' unmet needs, 2) socio-demographic and clinical characteristics of both PwD and caregivers, and 3) caregivers' burden and health-related outcomes that are related to caregivers' unmet needs. METHODS: The present analyses are based on cross-sectional data of n = 226 dyads of caregivers and their community-dwelling PwD participating in a comprehensive standardized, computer-based caregivers' needs assessment within a general practitioner (GP)-based, cluster-randomized intervention trial. RESULTS: A total of n = 505 unmet needs were identified for n = 171 caregivers from the intervention group at baseline. Only 24.3% caregivers reported no unmet need (n = 55), whereas 75.7% caregivers had at least one unmet need (n = 171). Caregivers had on average 2.19 unmet needs (mean = 2.19, SD = 2.15). Specifically, 53.1% of caregivers had one up to three unmet needs (n = 120), 18.6% (n = 42) had three up to six unmet needs, and 4.0% (n = 9) had more than six unmet needs. DISCUSSION: Our results underline the importance of a comprehensive needs assessment for family dementia caregivers to develop and implement concepts that can provide family dementia caregivers with optimal support.

Patients with Dementia in Primary Care: Who Is Referred to a Neurologist/Psychiatrist and What Patient-Oriented Factors Are Associated with the Visit? - Strohmaier, Urs; Keller, Felix; Kilimann, Ingo; Michalowsky, Bernhard; Wucherer, Diana; Zwingmann, Ina; Teipel, Stefan; Hoffmann, Wolfgang; Thyrian, Jochen René (J Alzheimers Dis, 2018)
BACKGROUND: The current guidelines imply that basic medical diagnostics for dementia should be provided by general practitioners in cooperation with other specialists such as neurologists and psychiatrists. OBJECTIVES: The aims of this paper were to 1) compare the dementia patients of general practice residents whose care is co-managed by neurology/psychiatry residents with those whose care is not; 2) identify the patient variables associated with the utilization of neurological and psychiatric specialists; and 3) describe the frequency of imaging used for dementia patients in primary care. METHODS: The analyses utilized data from 485 individuals who screened positive for dementia in primary care (PWD). Clinical variables and the utilization of specialists were assessed via medical records and face-to-face interviews. The factors associated with the utilization of specialists were assessed using multivariate linear regression and included age, sex, relationship status, cognitive impairment, depression, activities of daily living, and formal diagnosis of dementia. RESULTS: Our results show that 89 out of 485 study participants (18.4%) were referred to specialists 12 months prior to assessment. Of these 89 individuals, 14.6% (n = 13) did not receive imaging diagnostics, while 39.3% (n = 35) received brain imaging by CT scan and 46.1% (n = 41) by MRI. PWD referred to specialists differed from those not referred, in age, relationship status, and the presence of a formal diagnosis. Our multivariate analysis revealed that younger age (OR = 0.95; 95% -confidence interval 0.90-0.99; p = 0.04) and higher functional impairment (OR = 1.15; 95% -confidence interval 1.02-1.30; p = 0.02) were associated with a visit to a specialist. DISCUSSION: Only 1 out of every 4 to 5 individuals who have screened positive for dementia have visited a specialist in psychiatry or neurology. While in general, women utilized specialists less often than men, younger and more functionally impaired patients were more likely to be sent to a specialist by their treating general practitioner. Almost 90% of the patients sent to a specialist received cranial neuroimaging, suggesting high adherence to diagnostic guidelines in specialized care.

Potentially Inappropriate Medication in Community-Dwelling Primary Care Patients who were Screened Positive for Dementia. - Wucherer, Diana; Eichler, Tilly; Hertel, Johannes; Kilimann, Ingo; Richter, Steffen; Michalowsky, Bernhard; Thyrian, Jochen René; Teipel, Stefan; Hoffmann, Wolfgang (J Alzheimers Dis, 2017)
BACKGROUND: Potentially inappropriate medication (PIM) in older people is a risk factor for adverse drug effects. This risk is even higher in older people with dementia (PWD). OBJECTIVE: Our study aimed to determine (1) the prevalence of PIM among primary care patients who were screened positive for dementia and (2) the sociodemographic and clinical variables associated with the use of PIM. METHODS: DelpHi-MV (Dementia: life- and person-centered help in Mecklenburg-Western Pomerania) is a general practitioner-based, cluster-randomized, controlled intervention study to implement and evaluate an innovative concept of collaborative dementia care management in Germany. The comprehensive baseline assessment includes a home medication review. The present analyses are based on the data from 448 study participants (age 70+, DemTect <9). PIMs were identified using the list of Potentially Inappropriate Medications in the Elderly (Priscus). RESULTS: (1) A total of 99 study participants (22%) received at least one PIM. The highest prevalence was found for antidepressants, benzodiazepines, and analgetics. The most frequently prescribed PIMs were amitriptyline, etoricoxib, and doxazosin. (2) Use of a PIM was significantly associated with a diagnosis of a mental or behavioral disorder. CONCLUSIONS: The prescription rate of PIMs for community-dwelling PWD was comparable with the rates found for the general population of older people in Germany (20-29%). Antidepressants with anticholinergic properties and long-acting benzodiazepines were the most prescribed PIMs, despite having an unfavorable benefit-risk ratio. This high prevalence of PIM prescriptions in a vulnerable population of PWD indicates that standard care for dementia should include careful medication review and management.

Community-Dwelling People Screened Positive for Dementia in Primary Care: A Comprehensive, Multivariate Descriptive Analysis Using Data from the DelpHi-Study. - Thyrian, Jochen René; Eichler, Tilly; Michalowsky, Bernhard; Wucherer, Diana; Reimann, Melanie; Hertel, Johannes; Richter, Steffen; Dreier, Adina; Hoffmann, Wolfgang (J Alzheimers Dis, 2016)
BACKGROUND: Efficient help and care for people with dementia (PWD) is dependent on knowledge about PWD in primary care. OBJECTIVE: This analysis comprehensively describes community-dwelling PWD in primary care with respect to various dementia care specific variables. METHODS: The analyses are based on baseline data of the ongoing general practitioner-based, randomized, controlled intervention trial DelpHi-MV (Dementia: life- and person-centered help). 6,838 patients were screened for dementia in 136 GP practices; 17.1% were screened positive, 54.4% of those agreed to participate and data could be assessed in n = 516 subjects. We assessed age, sex, living situation, cognitive status, functional status, level of impairment, comorbidities, formal diagnosis of dementia, depression, neuropsychiatric symptoms, quality of life, utilization of medical support, and pharmacological therapy. RESULTS: Concerning clinical-, dementia-, and health-related variables, the sample under examination was on average mildly cognitively and functionally impaired (MMSE, m = 22.2; BADL, m = 3.7). A level of care was assigned in 38.0%. Depression was identified in 15.4% and other frequent comorbidities were high blood pressure (83.3%), coronary heart diseases (37.1%), cerebrovascular diseases (22.3%), among others. In 48.6%, neuropsychiatric symptoms were present in a clinically relevant severity. Pharmacological treatment with antidementia medication was received by 25.8% and antidepressant medication by 14.0%. Utilization of services was generally low. CONCLUSION: The comprehensive description of people screened positive for dementia in primary care reveals a complex and unique population of patients. They are considerably underdiagnosed and in their majority mildly to moderately affected. More in-depth analyses are needed to study relations, associations and interactions between different variables.

Economic Analysis of Formal Care, Informal Care, and Productivity Losses in Primary Care Patients who Screened Positive for Dementia in Germany. - Michalowsky, Bernhard; Thyrian, Jochen René; Eichler, Tilly; Hertel, Johannes; Wucherer, Diana; Flessa, Steffen; Hoffmann, Wolfgang (J Alzheimers Dis, 2016)
BACKGROUND: The majority of people with dementia (PwD) live at home and require professional formal care and informal care that is generally provided by close relatives. OBJECTIVE: To determine the utilization and costs of formal and informal care for PwD, indirect costs because of productivity losses of caregivers, and the associations between cost, socio-demographic and clinical variables. METHODS: The analysis includes the data of 262 community-dwelling PwD and their caregivers. Socio-demographics, clinical variables, and the utilization of formal care were assessed within the baseline assessment. To evaluate informal care costs, the Resource Utilization in Dementia (RUD) questionnaire was used. Costs were calculated from a social perspective. Associations were evaluated using multiple linear and logistic regression models. RESULTS: Formal care services were utilized less (26.3%) than informal care (85.1%), resulting in a cost ratio of one to ten(1,646 €; 16,473 €, respectively). In total, 29% of caregivers were employed, and every seventh (14.3%) experienced productivity losses, which corresponded to 1,258 € annually. Whereas increasing deficits in daily living activities were associated with higher formal and higher informal costs, living alone was significantly associated with higher formal care costs and the employment of a caregiver was associated with lower informal care costs. CONCLUSION: Informal care contributes the most to total care costs. Living alone is a major cost driver for formal costs because of the lower availability of potential informal care. The availability of informal care is limited and productivity losses are increased when a caregiver is employed.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Caregivers; Cost of Illness; Cross-Sectional Studies; Dementia; Female; Germany; Health Care Costs; Home Care Services; Humans; Male; Patient Care; Sensitivity and Specificity; Surveys and Questionnaires

Living Alone with Dementia: Prevalence, Correlates and the Utilization of Health and Nursing Care Services. - Eichler, Tilly; Hoffmann, Wolfgang; Hertel, Johannes; Richter, Steffen; Wucherer, Diana; Michalowsky, Bernhard; Dreier, Adina; Thyrian, Jochen René (J Alzheimers Dis, 2016)
BACKGROUND: Little is known about the proportion and the characteristics of community-dwelling people with dementia (PWD) living alone in Germany. OBJECTIVES: To analyze the prevalence of PWD living alone (with and without the support of an informal caregiver) and socio-demographical and clinical characteristics as well as health and nursing care utilization associated with living alone. METHODS: DelpHi-MV (Dementia: Life- and person-centered help in Mecklenburg-Western Pomerania) is a general practitioner-based, randomized controlled intervention trial. The present analyses are based on baseline data of 511 patients (≥70 years, community-dwelling) who had screened positive for dementia (DemTect <9). RESULTS: N = 251 (51%) of the patients lived alone. PWD living alone were statistically significantly more often female, older, and more often widowed than those not living alone. About 9% of the patients (n = 24) were not supported by any informal caregiver. Regarding the clinical variables (cognitive and functional impairment, depression, falls, number of drug-related problems, malnutrition, quality of life), there were no statistically significant group differences. Patients living alone utilized professional services such as home care, help with medication, home-delivered meals, or housekeeping assistance significantly more often. Multivariate analyses confirmed these findings. CONCLUSION: Our results reveal the high proportion of PWD living alone in Germany. PWD living alone did not seem to be at an increased health risk. Our findings indicate that living alone with dementia is possible. In order to ensure the sufficient provision of health and nursing care services for PWD living alone, providers should consider the present results for future planning.

Unmet Needs of Community-Dwelling Primary Care Patients with Dementia in Germany: Prevalence and Correlates. - Eichler, Tilly; Thyrian, Jochen René; Hertel, Johannes; Richter, Steffen; Wucherer, Diana; Michalowsky, Bernhard; Teipel, Stefan; Kilimann, Ingo; Dreier, Adina; Hoffmann, Wolfgang (J Alzheimers Dis, 2016)
BACKGROUND: To provide an optimal care for persons with dementia (PWD), their individual unmet needs have to be identified and comprehensively addressed. OBJECTIVES: Present analyses aim to describe the number and types of unmet needs of German primary care patients screened positive for dementia and factors associated with the number of unmet needs. METHODS: DelpHi-MV (Dementia: life- and person-centered help in Mecklenburg-Western Pomerania) is a general practitioner-based, cluster-randomized controlled intervention trial. Analyses are based on the baseline data of 227 PWD (≥70 years, living at home) of the intervention group who had screened positive for dementia (DemTect<9) and received a standardized computer-assisted needs assessment. RESULTS: PWD had on average 8.77±5.04 unmet needs (Range = 0-31). More than 90% of the PWD had three or more unmet needs. Unmet needs were identified across all predefined 26 subcategories. The majority of unmet needs occurred in the domains "nursing treatment and care" (38%), "social counseling and legal support" (20%), and "pharmacological treatment and care" (15%). More impairment in the activities of daily living was the only factor that was significantly associated with a higher number of unmet needs, independent of age, gender, living situation, presence of an informal caregiver, cognitive impairment, and depression. CONCLUSIONS: Present results demonstrate that community-dwelling PWD had a broad range of varying unmet needs. These findings emphasize the importance of a comprehensive needs assessment that allows the identification of individual needs as the basis for a tailored intervention- such as Dementia Care Management- that can address these needs.
Keywords: Aged, 80 and over; Caregivers; Cross-Sectional Studies; Dementia; Depression; Female; Germany; Health Services Needs and Demand; Humans; Male; Needs Assessment; Prevalence